ANALISIS TEBAL RIGID PAVEMENT DENGAN METODE BINA MARGA PD T-14-2013 (STUDI KASUS : SP. AIR HITAM – SP. GEMAR MENABUNG KOTA PEKANBARU) - Husni Mubarak; husnah husnah; Hasan Hasan (LPPM Universitas Abdurrab, 2019)
The intersection of Sudirman - the Soekarno Pekanbaru intersection road is a provincial road where the project work has been completed. The road is a place for passing passenger cars, light vehicles and heavy vehicles with varied vehicle axes. This research will discuss the rigid pavement design that has been issued by the Directorate General of Highways, namely Pd T-14-2003. The purpose of this study was to recalculate the thickness of the pavement using the Bina Marga Pd T-14-2003 method. Specifically conducted a comparative analysis of rigid pavement thickness using the Bina Marga Pd T-14-2003 method with existing conditions in the field. The calculation method for rigid pavement carried out is the HVAG (Heavy Vehicle Axle Group) method on the cement concrete pavement planning guide. After comparison analysis was obtained, the concrete cement pavement thickness in the field was 45 cm with 30 cm concrete plate thickness and 15 cm thinner concrete (Lc) while the theoretically calculated concrete cement cement pavement thickness was 33 cm with a thick concrete plate 18 cm which is the most economical plate thickness and thin concrete (Lc) is 15 cm.